Characterization of the novel HLA‐C*04:438 allele by next generation sequencing. (16th September 2021) - Jacob, Valentine; Farce, Fabienne; Kaveri, Rangolie; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐C*04:438 differs from HLA‐C*04:01:01 by one nucleotide substitution in codon 237 in exon 4.